Doxycycline-induced esophagitis: Report of two cases and review of the literature - Oktay Bulur (Dicle Medical Journal, 2010)
Although it is not so frequent in medical literature, drug-induced esophageal injury is important, because of its possible complications. Here, we reported two patients with ulcerative esophagitis secondary to doxycycline use. Both patients applied to outpatient clinic with retrosternal pain, odynofagia and dysphagia. Symptoms had been developed after three days of doxicycline treatment in the first patient, and after two days in the second patient. Upper gastrointestinal endoscopy revealed ulcers in patient 1 at the upper 1/3 segment of esophagus and in patient 2 at the middle 1/3 segment of esophagus. Based on the endoscopic findings, the patients were diagnosed as drug-induced esophageal injury resulting from doxycycline treatments. Doxycycline treatments were stopped and lansoprazole and sucralfate was started.